Former Yugoslav Republic of Macedonia : 2018 Article IV Consultation; Press Release; Staff Report; and Statement by the Executive Director for Former Yugoslav Republic of Macedonia. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2019)
More than twelve years after achieving candidate status, FYR Macedonia's prospects for opening accession negotiations with the European Union are looking hopeful for the first time. The end of the political crisis has revived structural reforms, but investment is yet to gain a strong footing amid lingering uncertainties. Structural policies should focus on addressing longstanding weaknesses in the labor market, judiciary, and public administration to boost productivity and achieve faster income convergence. Macroeconomic policies should support this goal by rebuilding buffers and maintaining financial stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet